2013
DOI: 10.1063/1.4793397
|View full text |Cite
|
Sign up to set email alerts
|

Improving the optical absorption of BiFeO3 for photovoltaic applications via uniaxial compression or biaxial tension

Abstract: First-principles computations are employed to investigate the electronic structures and optical absorption of rhombohedral BiFeO 3 under uniaxial compression and biaxial tension. We find that the bandgap of BiFeO 3 is reduced under uniaxial compression, and it can be tuned to the ideal value for photovoltaic applications; furthermore, the indirect-to-direct bandgap transition occurs, which would lead to much enhanced optical absorption near the band edge. Similar results are found for biaxial tensile strain. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 28 publications
(46 reference statements)
3
35
0
Order By: Relevance
“…f) Bandgap as a function of the uniaxial stress (−σ 33 ) with and without a scissor shift of the bandgaps by 0.54 eV (shifted data are indicated as corrected gap). Reproduced with permission . Copyright 2013, AIP Publishing.…”
Section: Nonhalide Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…f) Bandgap as a function of the uniaxial stress (−σ 33 ) with and without a scissor shift of the bandgaps by 0.54 eV (shifted data are indicated as corrected gap). Reproduced with permission . Copyright 2013, AIP Publishing.…”
Section: Nonhalide Perovskitesmentioning
confidence: 99%
“…Through DFT study of the effect of uniaxial compression and biaxial tension, Dong et al found that the bandgap of rhombohedral BiFeO 3 can be reduced to the ideal value of 1.34 eV for PV applications. Moreover, in this process, the bandgap is transformed from indirect to direct leading to an enhanced optical absorption, as shown in Figure f . Recently, Nechache et al investigated the multiferroic material Bi 2 FeCrO 6 (BFCO).…”
Section: Nonhalide Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The polarization increases nearly linearly from 75.5 to 97.1 μC cm −2 when the [111] stress changes from 8 to −8 GPa, which could tune the photoelectric, piezoelectric and ferroelastic properties of BiFeO 3 . When the polarization of BiFeO 3 increases from 75.5 to 97.1 μC cm −2 , optical absorption is expected to increase due to reduced band gap and the photocurrent is proportional to P , so that the photovoltaic efficiency will be significantly enhanced. On the other hand, piezoelectricity would decreases when P increases, because it is proportional to the elastic compliance coefficients.…”
Section: Calculated Lattice Constants (A and C In å) Polarization (Pmentioning
confidence: 99%
“…Motivated by the enhanced PV properties in graphene/ polycrystalline BFO/Pt heterostructure [19], we suggest the BFO/ TO heterojunctions would possess an improved PV response due to the BPVE in BFO. Moreover, the PV effect and electronic properties in pure BFO can be engineered by electric field [20,21] and strain [22,23]. Therefore, a tunable PV effect by strain and electric field would be expected in the heterostructures.…”
Section: Introductionmentioning
confidence: 98%